On local center-conforming spaces and including pseudogroup of the transformations - Kondaurov, M. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:М. Кондауров. О локальных центро-конформных пространствах и охватывающей псевдогруппе преобразованийM. Kondaurovas. Apie lokalinės centrokonforminės erdvės ir aprėpiamą transformacijų pseudogrupę